KINERJA PEGAWAI LOKA POM HULU SUNGAI UTARA DALAM PENGAWASAN DISTRIBUSI OBAT ILEGAL DI KABUPATEN HULU SUNGAI UTARA, BALANGAN, DAN TABALONG - Riduan, Akhmad (Al Iidara Balad, 2022)
To support organizational performance, both public and private, competent human resources are needed in their field of work. As one of the government institutions engaged in the supervision of the sale/circulation of illegal drugs, the presence of BPOM/Loka POM in various regions is necessary to protect consumers from various types of illegal drugs that are dangerous for consumption. In the Banua Enam area, Loka POM Hulu Sungai Utara which is located in Amuntai city, Hulu Sungai Utara, has a working area covering the Regencies of Hulu Sungai Utara, Balangan, and Tabalong so that organizational performance is at stake. This study uses a qualitative approach with a descriptive type of research where data is collected through observation, interviews, and documentation studies. The collected data were analyzed through data reduction, data display, and conclusion drawing/verification techniques and tested for credibility through extended observations, increased persistence, triangulation, negative case analysis, using reference materials, and member checks. In carrying out the performance of Loka POM Hulu Sungai Utara employees to supervise the sale/circulation of illegal drugs in North Hulu Sungai, Balangan, and Tabalong Regencies, cases of illegal drug sales/circulation were found, especially in Hulu Sungai Utara and Tabalong Regencies even though the quantity was from the 2019 range. -2021 experienced a decrease in the number of cases handled while in terms of quality, non-justitia and pro-justitia actions were taken against a number of cases of illegal drug sales/trafficking. The things above are related to the lack of staff availability, limited facilities and infrastructure and the available budget. In order to improve the performance of the Hulu Sungai Utara Loka POM employees, continuous employee development is needed by the Head of the Hulu Sungai Utara POM Loka, additional employees, especially in the inspection function, as well as increasing office facilities and infrastructure in addition to budget allocations that need to be increased. Apart from that, awareness and participation of all pharmacies/drug shop owners as well as consumer concern in reporting illegal drug sales/circulation are also needed.